48.5k views
2 votes
F f(x) = 3x – 2 and g(x) = 6 – 4x, find f(x) + g(x). Please include solution

User Gnllucena
by
5.0k points

2 Answers

1 vote

Answer:

-x+4 is the answer.

Explanation:

We have given two functions.

f(x) = 3x-2

g(x) = 6-4x

We have to find the addition of given two functions.

f(x)+g(x) = ?

Putting given values in above equation, we have

f(x)+g(x) = (3x-2)+(6-4x)

f(x)+g(x) = 3x-2+6-4x

adding like terms ,we have

f(x)+g(x) = (3-4)x+(6-2)

f(x)+g(x) = (-1)x + (4)

f(x)+g(x) = -x +4 which is the answer.

User Joshstrike
by
4.8k points
5 votes

Answer:


f(x)+g(x)=-x+4

Explanation:

We have the functions,
f(x)=3x-2 and
g(x)=6-4x.

It is required to find the sum of these functions.

That is,
f(x)+g(x).

On substituting the functions, we get,


f(x)+g(x)=(3x-2)+(6-4x)

i.e.
f(x)+g(x)=(3x-4x)+(6-2)

i.e.
f(x)+g(x)=-x+4

Thus, the sum of the functions i.e.
f(x)+g(x)=-x+4.

User Eloleon
by
5.0k points